Principles of blending fatty acid balanced vegetable oils - Топчій, Оксана Анатоліївна; Котляр, Євгеній Олександрович (Eastern-European Journal of Enterprise Technologies, 2015)
An effective method of obtaining fat products of a set fatty acid composition is blending (mixing) vegetable oils. The method is expedient since even cold-pressed oil composition is not optimal. Blended fat systems with a set ratio of polyunsaturated fatty acids (PUFAs) are effective in recipes that contain fat components, especially in meat products for functional and recreational nutrition. Two- and three-component blended systems are mathematically calculated. Composition of three-component vegetable oil blends is calculated at two stages. The purpose of the first stage is to identify the ratio of two main components, while the aim of the second stage is to calculate the share of the third component. The study presents findings on fatty acid composition of produced in Ukraine vegetable oils, which allows to prognosticate their use in blended systems. More accurate prognoses on possibilities of obtaining multi-component blended oils are possible due to the suggested mathematic method. We have modeled recipes of blended vegetable oils for foodstuffs, particularly for nutrition of healthy people, with correlation ω-6/ω-3—10:1, as well as for preventive nutrition—ω-6/ω-3 equal to 5:1. Оrganoleptic analysis of the established systems has proved that savoury peculiarities of each of the blended oils are reflected in the completed blend. The suggested technology is economically expedient since it does not require any peculiar expenses on additional equipment.